AN EMPIRICAL STUDY OF THE FORMATION OF ADDICTIVE BEHAVIOR IN ADOLESCENTS (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article studies the types of addictive behavior that adolescents are prone to, depending on age and gender, and makes a psychological analysis. Based on the results of the study, a conclusion is drawn.